Relationship Between The Characteristics Of The Wound And The Event Of Patient Infection - Darmila; Nadia Alfira; Muriyati; Andi Baso Tombong (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2020)
The results of observations at RSUD H. Andi Sultan Daeng Radja carried out observations on all types of wounds that entered the emergency room with each wound characteristic observed, namely the location of the wound, the shape of the wound, the size of the wound, the depth of the wound, and the wound edge. Research Objectives To determine the relationship between wound characteristics and infection incidence in RSUD H. Andi Sulthan Daeng Radja, Bulukumba Regency. The research design is quantitative research. This study used a cross-sectional design. The sample size is 14 people. Results Based on the Fisher exact test, the value of p = 0.005 (<α = 0.05) was obtained, which means that there is a significant relationship between the location of the wound and the incidence of infection. Kolmogorov Smirnov test results obtained p-value = 0.016 (<α = 0.05), which means that there is a significant relationship between the shape of the wound and the incidence of infection. Kolmogorov Smirnov test results obtained p-value = 0.010 (<α = 0.05), which means that there is a significant relationship between wound size and the incidence of infection. Kolmogorov Smirnov test results obtained p-value = 0.002 (<α = 0.05), which means that there is a significant relationship between wound depth and the incidence of infection. The Kolmogorov Smirnov test results obtained p-value = 0.267 (> α = 0.05), which means that there is no significant relationship between the wound edges and the incidence of infection. Conclusion and suggestion that there is a significant relationship between the location, shape, size, and depth of the wound and the incidence of infection. It is hoped that there will be further research with a larger number of samples with in-depth studies.